1994
DOI: 10.3950/jibiinkoka.97.2103
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the volume of the mastoid air cell system using digital image processing.

Abstract: There has been a great deal of controversy concerning the development of pneumatization in the temporal bone. Many reports on the size of the mastoid air cell system have been discussed a planimetric X-ray method, however , there have been no techniques for direct volume measurement based on high-resolution computed tomography (CT) . Discussion of the relationship between ear disease and pneumatization of the temporal bone requires three-dimensional measurement of the temporal bone in vivo. Recently, we develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Thus, people who have a wide mastoid system and an open eustachian tube have a greater risk of perforation of the tympanic membrane, due to the decreased protective role of air as a cushion [10]. While Ito et al [20] in their series of 25 cases found the mean total volume of 41 temporal bone air cells to be 4.05 B 1.59 ml, Isono et al [21] reported that it was 6 ml in 43 normal temporal bones. They did not observe any difference between the volumes of the right and left sides and between the two sexes.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, people who have a wide mastoid system and an open eustachian tube have a greater risk of perforation of the tympanic membrane, due to the decreased protective role of air as a cushion [10]. While Ito et al [20] in their series of 25 cases found the mean total volume of 41 temporal bone air cells to be 4.05 B 1.59 ml, Isono et al [21] reported that it was 6 ml in 43 normal temporal bones. They did not observe any difference between the volumes of the right and left sides and between the two sexes.…”
Section: Discussionmentioning
confidence: 96%
“…The method of evaluating pneumatization in this study was precise and convenient, and differed from the previous studies. [11][12][13][14][15][16][17][18] The volume of pneumatization including air cells and tympanic cavity was calculated and found to be similar to other studies. [13][14][15][16][17][18] It was found x The authors speculate that this information may be of help to surgeons that there were correlations between the pneumatization and all the measured parameters of the facial nerve.…”
Section: Discussionmentioning
confidence: 92%